2014
DOI: 10.1038/cddis.2014.282
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β/Smad3 inhibit vascular smooth muscle cell apoptosis through an autocrine signaling mechanism involving VEGF-A

Abstract: We have previously shown that in the presence of elevated Smad3, transforming growth factor-β (TGF-β) transforms from an inhibitor to a stimulant of vascular smooth muscle cell (SMC) proliferation and intimal hyperplasia (IH). Here we identify a novel mechanism through which TGF-β/Smad3 also exacerbates IH by inhibiting SMC apoptosis. We found that TGF-β treatment led to inhibition of apoptosis in rat SMCs following viral expression of Smad3. Conditioned media from these cells when applied to naive SMCs recapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…1, A-D). These observations are consistent with the effects of VEGF on the VSMC phenotypic switch and proliferation (34), suggesting that activated STAT3 signaling pathway is positively correlated with the synthetic VSMC phenotype.…”
Section: Activated Stat3supporting
confidence: 78%
See 1 more Smart Citation
“…1, A-D). These observations are consistent with the effects of VEGF on the VSMC phenotypic switch and proliferation (34), suggesting that activated STAT3 signaling pathway is positively correlated with the synthetic VSMC phenotype.…”
Section: Activated Stat3supporting
confidence: 78%
“…Correlates with VSMC Synthetic Phenotype-Previous studies have shown that VEGF is a key regulator of physiological and pathological angiogenesis, which inhibits VSMC apoptosis and promotes VSMC proliferation by suppressing the expression of VSMC marker genes (34,35). Our data revealed that although the STAT3 mRNA level in HAVSMCs was not significantly changed after incubating with 50 ng/ml VEGF for different time periods (12,24, and 48 h), the phosphorylated (p)-STAT3 protein expression was significantly elevated to 3-6-fold compared with control levels (Fig.…”
Section: Activated Stat3mentioning
confidence: 99%
“…Indeed, the data showed that Wnt2b, Wnt4, Wnt5a, and Wnt9a all stimulated SMC proliferation compared to the control (Figure 5A). The increase of SMC proliferation unlikely resulted from reduced apoptosis, considering that even basal level of apoptosis (active caspase-3) could not be detected unless apoptosis is induced[11]. Wnt11, which did not stabilize β-catenin, did not enhance SMC proliferation at either of the three concentrations used (Figure 5A) thereby reinforcing the functional specificity of the other 4 Wnts.…”
Section: Resultsmentioning
confidence: 81%
“…In fact, vascular SMCs are hardy cells. Generally they do not undergo apoptosis until induced with an apoptotic factor such as UV[11]. Taken together, these findings demonstrate that increases in β-catenin can increase SMC proliferation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation